(Extreme) political polarization and party patronage. Issue 2 (3rd April 2022) - Kopecký, Petr; Meyer-Sahling, Jan-Hinrik; Spirova, Maria
ABSTRACT: The contemporary literature on political parties has identified their gradual but consistent shift away from civil society and towards the state. As parties are becoming ever increasingly dependent on state resources and exclusively interested in governing, as Mair ( Ruling the void: The hollowing of western democracy [Verso Books, 2013]) suggested, and patronage is a fundamental to that relationship, the degree and modes of party patronage becomes pivotal to understanding their performance, and the ways they organize and govern. In this paper we argue that party patronage is likely to be structured by the nature of political competition and explore the effects of political polarization, which is a feature of political competition relatively independent from the precise format of a party system, on patronage practices. We advance a theoretical argument which systematically links different types of political polarization with different patterns of party patronage, arguing that extreme polarization incentivizes political parties to develop heavily partisan strategies of party patronage which, in turn, further fuel political polarization. Thus, we also contribute to burgeoning literature on political polarization and its negative effects on the functioning of both political parties and overall political systems.